Responsibility for human rights : transnational corporations in imperfect states / David Jason Karp. - Karp, David Jason (Cambridge studies in international relations ;, 2014)
Responsibility for Human Rights provides an original theoretical analysis of which global actors are responsible for human rights, and why. It does this through an evaluation of the different reasons according to which such responsibilities might be assigned: legalism, universalism, capacity and publicness. The book marshals various arguments that speak in favour of and against assigning 'responsibility for human rights' to any state or non-state actor. At the same time, it remains grounded in an incisive interpretation of the world we actually live in today, including: the relationship between sovereignty and human rights, recent events in 'business and human rights' practice, and key empirical examples of human rights violations by companies. David Karp argues that relevantly public actors have specific human rights responsibility. However, states can be less public, and non-state actors can be more public, than might seem apparent at first glance.